Against the Spirit of System - JOHN HARLEY WARNER (Princeton University Press, 2014)
Out of the reorganization of medicine in the wake of the French Revolution, the Paris hospitals emerged as the most vibrant center of Western medicine. What has come to be called the Paris Clinical School is broadly identified with a distinctive complex of institutional arrangements, clinical techniques and teaching practices, modes of organizing knowledge, and structures of medical perception that characterized Paris medicine between 1794 and the mid-nineteenth century. After Waterloo and peace, Paris became a Mecca for foreign medical students and practitioners. Between 1815 and the 1850s, some one thousand crossed the Atlantic from the United States to study in the hospitals and dissecting rooms of the French capital, and many times that number made shorter journeys across the Rhine from German states and across the Channel from Britain.